2018
DOI: 10.1038/s41422-018-0076-9
|View full text |Cite
|
Sign up to set email alerts
|

The RNA-binding protein ROD1/PTBP3 cotranscriptionally defines AID-loading sites to mediate antibody class switch in mammalian genomes

Abstract: Activation-induced cytidine deaminase (AID) mediates class switching by binding to a small fraction of single-stranded DNA (ssDNA) to diversify the antibody repertoire. The precise mechanism for highly selective AID targeting in the genome has remained elusive. Here, we report an RNA-binding protein, ROD1 (also known as PTBP3), that is both required and sufficient to define AID-binding sites genome-wide in activated B cells. ROD1 interacts with AID via an ultraconserved loop, which proves to be critical for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
38
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 67 publications
0
38
0
Order By: Relevance
“…31 Chen et al showed that ROD1 regulated transcription and was required for defining AID-loading sites to mediate antibody class switching with a PTBP3 deletion in mammalian genomes. 32 In melanoma, Huang et al identified that MEX3B decreased the susceptibility of cancer immunotherapy by targeting HLA-A. 33 Therefore, exploring the precise roles of In summary, this study first characterized the frequent downregulation of SORBS2 in HCC and showed the antitumour function of SORBS2 on the malignant phenotypes of HCC cells, including cell proliferation, migration, invasion, cell cycle progression and EMT both in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…31 Chen et al showed that ROD1 regulated transcription and was required for defining AID-loading sites to mediate antibody class switching with a PTBP3 deletion in mammalian genomes. 32 In melanoma, Huang et al identified that MEX3B decreased the susceptibility of cancer immunotherapy by targeting HLA-A. 33 Therefore, exploring the precise roles of In summary, this study first characterized the frequent downregulation of SORBS2 in HCC and showed the antitumour function of SORBS2 on the malignant phenotypes of HCC cells, including cell proliferation, migration, invasion, cell cycle progression and EMT both in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 87%
“…For example, Zhao et al demonstrated that RPS3 post‐transcriptionally upregulated the mRNA of its target gene SIRT1 to mediate hepatocarcinogenesis . Chen et al showed that ROD1 regulated transcription and was required for defining AID‐loading sites to mediate antibody class switching with a PTBP3 deletion in mammalian genomes . In melanoma, Huang et al identified that MEX3B decreased the susceptibility of cancer immunotherapy by targeting HLA‐A .…”
Section: Discussionmentioning
confidence: 99%
“…Several scenarios could explain the inhibition of CSR to IgG1 by I exon dss ASOs. First, RNA-binding proteins have been shown to interact with AID 22,4042 and the ASO, attached to the GLTs, could avoid fixation of such proteins necessary for CSR. Second, it has been described that, when the accumulation of intronic switch RNAs was prevented from the onset of CH12F3-2A B cells stimulation, R-loop levels were decreased by half in S regions 24 .…”
Section: Discussionmentioning
confidence: 99%
“…4,5 How convergent transcription attracts AID to off-targets, and whether or not it is involved in on-target activity at Ig loci has not been fully elucidated. The study by Chen and colleagues, which is reported recently in Cell Research, 6 shed some light on this question.…”
mentioning
confidence: 98%